2021
DOI: 10.1007/s43393-021-00055-7
|View full text |Cite
|
Sign up to set email alerts
|

CcpA mutants influence selective carbon source utilization by changing interactions with target genes in Bacillus licheniformis

Abstract: The gram-positive bacterium Bacillus licheniformis exhibits obvious selective utilization on carbon sources. This process is mainly governed by the global regulator catabolite control protein A (CcpA), which can recognize and bind to multiple target genes that are widely distributed in metabolic pathways. Although the DNA-binding domain of CcpA has been predicted, the influence of key amino acids on target gene recognition and binding has yet to be uncovered. In this study, the impact of Lys31, Ile42 and Leu56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Glucose is a preferred carbon source that can be quickly used to produce energy and metabolites in bacilli, including for the production of acetoin, 2,3-butanediol, acetic acid and so on [ 35 ]. A previous study has demonstrated that CcpA mutants can affect the use of other carbon sources and the synthesis of related metabolites in the presence of glucose [ 36 , 37 , 38 ]. In order to further research the regulation mechanism of CcpA on glucose utilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose is a preferred carbon source that can be quickly used to produce energy and metabolites in bacilli, including for the production of acetoin, 2,3-butanediol, acetic acid and so on [ 35 ]. A previous study has demonstrated that CcpA mutants can affect the use of other carbon sources and the synthesis of related metabolites in the presence of glucose [ 36 , 37 , 38 ]. In order to further research the regulation mechanism of CcpA on glucose utilization.…”
Section: Resultsmentioning
confidence: 99%
“…B. licheniformis CA is a strain constructed by knocking out the ccpA on the basis of B. licheniformis . The method of ccpA gene knockout is carried out according to the method we reported earlier [ 36 ]. pET28a-CcpA was the plasmid used for the expression of CcpA.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the ps09-vgb fragment was cloned into pNZTT-D1 using the Sal I restriction site, and plasmid pNZTT-D2 was obtained. The gene knockout was performed according to the homologous recombination method, 43 and then, mutants BL2S and BL2K were constructed (Figure S4).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Improvement can be made by artificial mutation in the recognized nucleic acid binding region [76] , [77] , [78] . For the modification of transcription factors, site-directed mutagenesis strategy is usually adopted to meet the specific needs in application [79] , and the understanding of the mechanism can be built at the molecular-level [80] , [81] , [82] .…”
Section: Present and Potential Application For Synthetic Biologymentioning
confidence: 99%